Satu analisis kualitatif terhadap faktor pendorong pembayaran zakat oleh syarikat / Adibah Abdul Wahab - Abdul Wahab, Adibah (Center for Islamic Philantrophy & Social Finance (CIPSF), 2019)
This research is conducted to investigate factors that influenced zakat payment among companies or business entities. The study is based on qualitative analysis conducted on decision makers at 14 companies. This research uses semi structured interview format and use thematic technique for data analysis. The result shows that, efforts done by zakat institutions, actions taken by government and internal initiatives are the three main factors. Excellent customer service, efficient disbursement and good governance are the three main component for zakat institutions. Tax rebate, tax deductions, fatwa rulings and enforcement are the elements for governments’ role that can affect zakat payment. However internal motivation factors are the most dominant. It consists of three elements i.e. Board Directors understanding, Muslim Board Directors composition and company financial status. Above all, Board Directors understanding is the most crucial. Therefore, marketing effort should be focusing on decision makers of the companies through understanding their behavior. This study contributes to the theory and gives insight on factors affecting zakat payment by business entity.